A linear Kalman Notch Filter for Power-Line Interference Cancellation - Sameni, R. (2012 16th CSI International Symposium on Artificial Intelligence and Signal Processing, 2012)
A discrete-time linear Kalman filter is presented for removing power-line interference from biomedical recordings. The theoretical aspects of this filter, the relationship with conventional digital IIR and adaptive IIR notch filters, and its steady state behavior are studied in detail. As compared to previous studies, the filter is linear and does not require any information about the amplitude nor the phase of the power-line interference. The proposed method is fairly general and is applicable to broad classes of signals contaminated by periodic noise. The proposed model also accounts for multiple harmonics. Two examples of its applications for electrocardiogram and electroencephalogram denoising are presented.